Association of Cardiac Troponin I Levels with the Severity of Coronary Artery Disease in Non-ST Elevation Myocardial Infarction - Mahmood, Khaled; Arefin, Md Minhaj; Rahman, M Mizanur; Jafar, Abul Hasnat Md; Ahmed, Nishat; Islam, Md Shafiqul; Ahsan, Mohammad Morshedul; Islam, Neena; Mojumder, Forhad Karim; Azam, MG (University Heart Journal, 2024)
Background : Among the acute coronary syndromes (ACS), Non-ST-elevation myocardial infarction (NSTEMI) is the most common presentation and a leading cause of hospital admissions. Prognosis of patients with ACS are related to the magnitude of cardiac biomarker release. Hence it is essential to see the relationship of increase in troponin levels in the setting of NSTEMI with the severity of CAD. Objective: This study was conducted to determine the association of cardiac troponin I (cTnI) with the severity of coronary artery disease in NSTEMI. Method : A cross-sectional analytical study was conducted on 120 NSTEMI patients admitted in National Institute of Cardiovascular Diseases, Dhaka between August 2016 to March 2017. cTnI was measured using IMMULITE 1000 (Siemens, USA) which is a three-step assay, based on the immunochemistry technology. All patients underwent coronary angiography in the index hospitalization. Stenosis > 70% in any of the three major epicardial vessels was considered significant CAD. Extent of CAD was defined as significant single, two or three vessel CAD. Chi-square test was applied to test the association between cTnI levels and CAD extent. Severity of coronary artery disease was also analysed by Vessel score and Gensini score. Spearmen’s Rank correlation test & Pearson’s correlation test were applied to test the association of cTnI with Vessel score and Gensini score respectively. Results: In the study, out of 120 patients, in 58 patients with cTnI levels < 10 folds upper limit of normal(ULN) (Group-I), (14) 24.1 % of the patients had single vessel, (18)31% had two vessel and (15)25.9 % had three vessel significant CAD, while among patients with cTnI levels > 10 folds ULN (Group-II) ,(11) 17.7 % of the patients had single vessel, (16)25.8% had two vessel and (29) 48.6% had three vessel significant CAD.There was an insignificant association between the cTnI levels and single vessel, two vessel CAD extent (p= 0.38, p= 0.52 respectively), however there was a statistically significant association between the cTnI levels and three vessel CAD (p=0.03) and also cTnI levels and multivessel disease (combined double vessel and triple vessel disease) (p=0.04). Mean vessel score was higher in group II than group I (2.101.02 vs. 1.641.07) with statistical significant difference (p=0.02). Mean Gensini Score was significantly higher in group II compared to group I (61.5±37.6 vs. 39.6±27.4, p<.001).There is a positive correlation between cTnI and coronary artery disease severity in terms of Gensini score (r=0.40, p=0.01).there is also a positive correlation between cTnI and coronary artery disease severity in terms of vessel score (r=0.28,p=0.01). Conclusion: Higher cTnI levels in NSTEMI are associated with severe CAD in the form of multi-vessel involvement with higher vessel score and Gensini score . Early coronary angiography should be considered especially in these patients & earlier revascularization would improve their clinical outcomes. University Heart Journal 2023; 19(2): 37-44